Accuracy of Intraoperative Examination in Central Nervous System Lesions: A Study of 133 Cases. - Balsimelli, Ludmila Barbosa de Souza; Oliveira, Jamille Costa de; Adorno, Flora Ávila; Brites, Clarissa Almeida; Bublitz, Giuliano Stefanello; Tavares, Lara Cristina de Carvalho; Coelho, Karina Munhoz de Paula Alves; Stall, Jaqueline; França, Paulo Henrique Condeixa de (Acta Cytologica, 2019)
Objective: Intraoperative examination is a highly valuable tool for the evaluation of central nervous system (CNS) lesions, helping the neurosurgeon to determine the best surgical management. This study aimed to evaluate the accuracy and to analyze the diagnostic disagreements and pitfalls of the intraoperative examinations through correlation with the final histopathological diagnosis in CNS lesions. Study Design: Retrospective analysis of intraoperative examination of CNS lesions and their final diagnosis obtained during 16 consecutive years. All diagnoses were reviewed and classified according to World Health Organization (WHO) grading for CNS tumors. Squash was performed in 119 cases, while frozen section and both methods were done in 7 cases each. Results: Among the 133 intraoperative examinations considered, 114 (85.7%) presented concordance and 19 (14.3%) diagnostic disagreement when compared with subsequent histopathological examinations. The sensitivity and specificity for the detection of neoplasia in intraoperative examination was 98 and 94%, respectively. The positive and negative predictive values were 99 and 88%, respectively. The accuracy for neoplastic and nonneoplastic disease was 85.7%. Disagreements were more frequent among low-grade (WHO grades I and II) neoplasms and nonmalignant cases. Conclusions: Our results showed good accuracy of the intraoperative assessments for diagnosis of CNS lesions, particularly in high-grade (grades III and IV) lesions and metastatic neoplasms.